Experimental Salmonellosis X. Cellular Immunity and Its Antibody in Mouse Mononuclear Phagocytes - Kurashige, Satonori (1967)
A cell-associated antibody was detected in the peritoneal mononuclear phagocytes (referred to as monocytes) of mice hyperimmunized with live vaccine of Salmonella enteritidis, by use of immune transfer and immune adherence hemagglutination techniques. The cellular antibody inhibited the growth of a virulent strain of S. enteritidis with the aid of complement and lysozyme on nutrient agar plates. This type of bactericidal antibody could not be detected in the monocytes of mice immunized with killed vaccine of S. enteritidis. The antibody extracted from the peritoneal monocytes of mice hyperimmunized with live vaccine was identified as a macroglobulin by ultracentrifugal analysis.